Productive and reproductive performances of hilly chicken at Naikhongchari hilly areas, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A total of 225 native Hilly chickens (152 females and 73 males) were reared in colony cages as large, medium and small body size groups for 10 months period to compare their production performances. The mean body weights of adult female and male birds were 2129, 1786 and 1457g; and 2436, 2834 and 2249 g respectively. The age of first egg were 158, 147 and 140 days and hen-day egg production were 44.56 ± 0.5, 46.15 ± 0.5 and 48.84 ± 0.7 percent (P